Tafsir Faidh Ar-Rahmān By Kh. Sholeh Darat: Method, Stylistic Features (Corak), And Indonesian Localization - Ikhwan Ansori; Idil Hamzah (The Ulama Cadre Education Program of Great Mosques of Istiqlal (PKUMI), 2024)
The emergence of Qur'anic commentaries and translations in local languages reflects the influence of the socio-cultural context of the interpreters, where Qur'anic exegesis is an intellectual construct aimed at actualizing the message of revelation according to societal needs. This study examines Tafsīr Fayḍ al-Raḥmān by Kiai Shaleh Darat as a representation of the internalization of Javanese culture within Islam, creating a distinct style of exegesis based on local wisdom. This work was written in Javanese using Arabic Pegon script as a da'wah strategy and intellectual resistance against Dutch colonialism in the late 19th century. The use of Javanese was intended to facilitate understanding among the general public while circumventing the colonial government's prohibition on translating religious texts. The analysis shows that this commentary not only served as a tool for religious education but also as a medium for preserving cultural identity and symbolic resistance against colonial hegemony. This research is a descriptive-analytical study employing a historical approach by exploring the socio-political background and intellectual network of Kiai Shaleh Darat. The findings reveal that Tafsīr Fayḍ al-Raḥmān represents the dialectic between sacred text and local reality through contextual interpretation methods, while affirming the role of Nusantara scholars as agents of culturally rooted Islamization.